A Negative Association of Hypothalamic Volume and Perceived Stress in Patients with Atopic Dermatitis - Hideki Mochizuki; Christina Schut; Alina Shevchenko; Rodrigo Valdes-Rodriguez; Leigh A. Nattkemper; Gil Yosipovitch (Medical Journals Sweden, 2020)
Abstract is missing (Short communication)